Розв’язання завдань комплектування агрегату у складі культиватора ALTAIR-8,4 виробництва ПАТ «Ельворті» - Турчин, Р. О. (ТДАТУ, 2019)
EN: The method of aggregating the cultivator-plant-nutrient aggregate has been improved by choosing the right placement of its lateral sections and technological capacities, while ensuring the dosage, transport and distribution of mineral fertilizers from them to the working organs for fertilizing plants. The cultivator is improved by additional equipment with its lateral links with supporting self-aligning wheels, which are hinged to the central beam at an acute angle to the direction of movement of the unit. UK: Обґрунтована схема та експлуатаційні показники роботи культиваторного агрегату для міжрядного обробітку посівів просапних культур у складі трактора Білорус-1221 і культиватора ALTAIR-8,4, використання якого дає змогу підвищити тягово-зчіпні властивості агрегатуючого трактора, керованість і стійкість його руху.
Keywords: культиватор ALTAIR-8,4; трактор ХТЗ-160; трактор Білорус-1221; машини та обладнання в АПК